That Unforgettable Day--The Great Tokyo Air Raid through Drawings あの日を忘れない・描かれた東京大空襲 - Sumida Local Culture Resource Center (墨田郷土文化資料館); Bret Fisk (Japan Focus)
These memorable paintings depicting the Great Tokyo Air Raid of March 10, 1945 were featured in a special exhibit hosted by the Sumida Local Culture Resource Center in 2004. The Center staff originally settled on the idea of collecting amateur and professional artwork as a unique way of contributing to the preservation of the public memory regarding the March 10 incendiary air raid. Each painting is accompanied by a short explanatory text written by the artist. As well as giving insight into the particular scene depicted in the painting, these explanations generally touch on the artist's overall air raid experience. The paintings were published as part of a greater collection in 2005 as That Unforgettable Day-The Great Tokyo Air Raid Through Drawings.